Different distribution patterns of β-caryophyllene in the organs of mice between oral administration and inhalation - Higashihara, Mayo; Matsui, Nobutaka; Sumi, Tomoko; Yamaguchi, Taichi; Yoshioka, Yuri; Matsumura, Shinichi; Moriyama, Tatsuya; Zaima, Nobuhiro (Food Science and Technology Research, 2024)
β-caryophyllene (BCP) is a volatile bicyclic sesquiterpenoid found in essential oils from spices and edible foods such as black pepper, basil, and cloves. Orally administered BCP exhibits several bioactivities, including anti-inflammatory and antioxidant effects. In addition to its physiological function as a functional food factor, BCP is volatile. BCP inhalation has been reported to exhibit several bioactivities, suggesting that inhaled BCP is as bioactive as orally administered BCP. Recent studies have shown that both orally administered and inhaled BCP can be transferred to the serum and organs. No studies have compared the distributions of orally administered and inhaled BCP. Therefore, this study compared the distribution patterns for orally administered and inhaled BCP in mice. Our findings showed that the distribution patterns differed between oral administration and inhalation. Consequently, the effects of BCP on biological activity may differ between oral and inhalation routes.